2014
DOI: 10.1152/jn.00410.2014
|View full text |Cite
|
Sign up to set email alerts
|

Visual selectivity for heading in the macaque ventral intraparietal area

Abstract: Kaminiarz A, Schlack A, Hoffmann KP, Lappe M, Bremmer F. Visual selectivity for heading in the macaque ventral intraparietal area. J Neurophysiol 112: 2470 -2480, 2014. First published August 13, 2014 doi:10.1152/jn.00410.2014.-The patterns of optic flow seen during self-motion can be used to determine the direction of one's own heading. Tracking eye movements which typically occur during everyday life alter this task since they add further retinal image motion and (predictably) distort the retinal flow patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…However, these previous studies used stimuli containing insufficient visual cues (e.g., lack of depth cue), and this potentially undermined the retinal contributions. In particular, recent neurophysiologic studies using novel optic‐flow stimuli (with enriched visual cues, e.g., depth and perspective cues) have shown that the retinal mechanism played a dominate role in distortion compensation at the single‐neuron level (Bremmer, Kubischik, Pekel, Hoffmann, & Lappe, ; Kaminiarz, Schlack, Hoffmann, Lappe, & Bremmer, ; Manning & Britten, ; Sunkara, DeAngelis, & Angelaki, ). Our result of training‐induced improvement in self‐motion perception without actual eye movement appears to add a new twist to this retinal versus extraretinal debate.…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies used stimuli containing insufficient visual cues (e.g., lack of depth cue), and this potentially undermined the retinal contributions. In particular, recent neurophysiologic studies using novel optic‐flow stimuli (with enriched visual cues, e.g., depth and perspective cues) have shown that the retinal mechanism played a dominate role in distortion compensation at the single‐neuron level (Bremmer, Kubischik, Pekel, Hoffmann, & Lappe, ; Kaminiarz, Schlack, Hoffmann, Lappe, & Bremmer, ; Manning & Britten, ; Sunkara, DeAngelis, & Angelaki, ). Our result of training‐induced improvement in self‐motion perception without actual eye movement appears to add a new twist to this retinal versus extraretinal debate.…”
Section: Discussionmentioning
confidence: 99%
“…In complex goal-directed sensorimotor tasks, such as self-motion, sensory stimuli are typically the consequence of one's own action. As an example, the visual optical flow arriving at the retina is the direct consequence of moving forward and hence is predictable (Kaminiarz et al, 2014). Accordingly, and in line with the predictive coding framework, optic flow responses during self-induced (visually simulated) selfmotion might be suppressed.…”
Section: Introductionmentioning
confidence: 86%
“…Nevertheless, perceptual performance could be further enhanced if single neurons were capable of deducing heading information from visual signals alone. Accordingly, in two recent studies, we investigated if neurons in areas MST and VIP can encode heading solely based on visual signals (Bremmer et al, 2010;Kaminiarz et al, 2014). More specifically, we asked if such neurons would keep their heading selectivity regardless of whether or not the retinal flow resulting from a simulated forward motion was disturbed by superimposed simulated eye movements of various gains.…”
Section: Eye-movement Invariant Heading Encoding In Monkeysmentioning
confidence: 99%
“…All procedures were in accordance with published guidelines on the use of animals in research (European Communities Council Directive 86/609/ECC). Experimental methods followed standard procedures that were described in detail in (Bremmer et al, 2009(Bremmer et al, , 2010Morris et al, 2012, andKaminiarz et al, 2014). Optic flow stimuli were back projected onto a tangent screen (90° x 90°) 48 cm in front of the monkey and simulated self-motion of a virtual observer over an extended horizontal plane located 37cm below eye-level.…”
Section: Eye-movement Invariant Heading Encoding In Monkeysmentioning
confidence: 99%